Simulation of metabolism-based herb-drug interaction: towards safe and efficacious use of NIPRD-AM1 - Bulus Adzu; Kudirat Bola Mustapha; Collen Masimirembwa; Obiageri Obodozie; Rukaiyatu Abdullahi Kirim; Karniyus Shingu Gamaniel (Mashhad University of Medical Sciences, 2013)
Objective: To evaluate the effect of NIPRD-AM1 on CYP3A4 in order to generate clinically significant data for its safe and efficacious use. Materials and Methods: NIPRD-AM1 is a phytomedicine developed from aqueous root extracts of Nauclea latifolia Smith (Rubiaceae) for the treatment of uncomplicated malaria. The effect of NIPRD-AM1 on CYP3A4 was measured with and without the addition of NIPRD-AM1, by testing different concentrations of the product at 37 °C in reactive mixtures with ketoconazole (2.5 µM) as the positive control. Results: Results showed a very low IC50 value of 0.01 mg/ml similar to that of ketoconazole (0.016 mg/ml). Conclusion: Metabolic processes of NIPRD-AM1 are likely to inhibit CYP3A4, with potential implication on drugs that are CYP3A4 substrates. This is a promising approach for guidance towards the safe and efficacious use of NIPRD-AM1.